The puzzling association between inventory and auditor pricing in China - Xi Wu; Xueqin Wang; Yulong Yang (China Journal of Accounting Research, 2018)
The theory of audit pricing suggests that audit fees are positively associated with areas of higher inherent risk. Inventory is commonly cited as one such area, and many Western studies have reported a positive association between inventory and audit fees. However, most Chinese studies have reported a significant negative association. This study finds that this puzzling association is attributable to Chinese auditors charging a significant discount on the opening balance of inventory, whereas their U.S. counterparts charge a significant premium. Meanwhile, we show that opening-balance inventory is associated with higher inherent risk both in China and the U.S. On the other hand, both Chinese and U.S. auditors charge a significant discount on the net increase in inventory as of the current year end, and we show that this is associated with lower inherent risk. Therefore, Chinese auditors appear to underreact to the inherent risk associated with opening-balance inventory, which helps explain the puzzling negative association between inventory and audit fees in China.
Keywords: 650; Inventory; Audit fees; Inherent risk; China